Pregabalin-associated Elevation of Clozapine Serum Levels - Gahr, M.; Schmid, M. M.; Schönfeldt-Lecuona, C. (Pharmacopsychiatry, 2012)
We report our experience with a 34-year-old patient with schizophrenia, paranoid subtype, who demonstrated an elevation of clozapine serum levels subsequent to pregabalin comedication used for the treatment of schizophrenic anxiety. This observation turned to be dose-dependent. Although the pharmacokinetic profile of pregabalin suggests an exclusive renal elimination, our report supports the presumption of a possible direct or indirect hepatic “effect” of pregabalin.
Keywords: pharmacokinetics; schizophrenia treatment; antipsychotic drugs; adverse effects; schizophrenia